GeoDetector analysis of spatio-temporal patterns and driving mechanisms of farmland spatial transition within 897 counties in the Yangtze River Economic Belt, China - Shangan Ke; Haiying Cui; Xinhai Lu (Humanities & Social Sciences Communications)
Abstract This study examines 897 counties in the Yangtze River Economic Belt and develops a framework to evaluate farmland spatial transition, comprising four subsystems: scale, regularization, agglomeration, and specialization. It further investigates the driving forces underlying these transitions to provide robust scientific evidence for the sustainable management of farmland in the region. The findings are as follows: (1) From 2000 to 2020, the farmland spatial transition index in the Yangtze River Economic Belt showed no significant dynamic convergence or divergence, with spatial disparities remaining relatively stable over time. (2) The farmland spatial transition index fluctuated between 0.38 and 0.84, exhibiting a heterogeneous spatial pattern characterized by higher values in the eastern and western regions and lower values in the central region. Over the study period, the overall index showed a consistent upward trend. (3) Farmland spatial transition arises from the interplay of natural and socio-economic factors, with elevation exerting the strongest influence, as indicated by q-values ranging from 0.61 to 0.64. (4) Ecological and risk zone detection further confirm the dominant role of elevation in farmland spatial transition, while farmland endowment also demonstrates considerable explanatory power. Formulating agricultural development policies must integrate ecological protection with farmland utilization, particularly in high-elevation or ecologically vulnerable areas.